Focused Ultrasound and Microbubbles-Mediated Drug Delivery to Brain Tumor - Wu, Sheng-Kai (Pharmaceutics, 2020)
The presence of blood–brain barrier (BBB) and/or blood–brain–tumor barriers (BBTB) is one of the main obstacles to effectively deliver therapeutics to our central nervous system (CNS); hence, the outcomes following treatment of malignant brain tumors remain unsatisfactory. Although some approaches regarding BBB disruption or drug modifications have been explored, none of them reach the criteria of success. Convention-enhanced delivery (CED) directly infuses drugs to the brain tumor and surrounding tumor infiltrating area over a long period of time using special catheters. Focused ultrasound (FUS) now provides a non-invasive method to achieve this goal via combining with systemically circulating microbubbles to locally enhance the vascular permeability. In this review, different approaches of delivering therapeutic agents to the brain tumors will be discussed as well as the characterization of BBB and BBTB. We also highlight the mechanism of FUS-induced BBB modulation and the current progress of this technology in both pre-clinical and clinical studies.